Does training change mechanics ? An experimental study of the effect of participation in training on the mechanistic structuring of auditor judgment in Cameroon - MINKO Gervais Félix; ELLE, Narcisse; HANKO Osée (Revue du contrôle, de la comptabilité et de l’audit, 2022)
This research analyses the effect that external training on independence of judgment can have on the mechanistic/organic structuring of auditor judgment. It is interested in the hypothesis of a progression in the structuring of the auditor’s judgment following his participation in a training of external origin, and analyzes the conflict between the internal mechanisms (rules and internal procedures specific to audit bureau and their operating mechanism) and the external mechanisms (order of accounting professionals, external training) in structuring its judgment. Data is collected by means of semi-structured interviews with four auditors who have participated in training, in particular before and after the training. The comparison of these data with an ideal type of mechanistic and organic structuring, reveals two strong tendencies. For auditors with strong mechanistic characteristics at the start, training can consolidate the mechanistic structuring of judgment, or moderate it without calling it into question. The auditors concerned keep their mechanistic auditor profile. On the other hand, among auditors who present a rather organic profile before the training, the training seems to have no significant effect on their judgment mechanism. They keep their organic tendency after training.